Biomechanical Evaluation of Suture Configurations in Lesser Toe Plantar Plate Repairs. (July 2018) - Finney, Fred T.; Lee, Simon; Scott, Jaron; Irwin, Todd A.; Holmes, James R.; Talusan, Paul G.
Background: Lesser toe metatarsal-phalangeal (MTP) joint instability can be a major source of pain and dysfunction. Instability occurs when there is incompetence of the plantar plate and/or collateral ligaments. Newer operative treatments focus on performing anatomic repairs of the plantar plate. The goal of this study was to compare the biomechanical properties of 3 suture configurations that may be used for plantar plate repairs. Methods: Biomechanical analysis of 27 lesser toe plantar plates from fresh frozen human cadavers was completed. The plantar plate was detached from the proximal phalanx, and suture was placed in the distal plantar plate in a horizontal mattress, luggage-tag, or Mason-Allen suture configuration. Cyclic loading followed by load-to-failure testing was performed. Results: There was a significant difference in peak load-to-failure force between constructs (mattress: 115.53 ± 15.95 N; luggage-tag 102.42 ± 19.33 N; Mason-Allen: 89.96 ± 15.78 N; P = .015). Post hoc analysis demonstrated that the mattress configuration had significantly higher load-to-failure force compared with the Mason-Allen configuration ( P = .004). There were no significant differences between the mattress and the luggage-tag configurations or the luggage-tag and the Mason-Allen configurations. There were no differences in construct stiffness, axial displacement at the time of failure, or number of cycles required to produce 2 mm of displacement. Conclusion: The mattress configuration demonstrated better peak load-to-failure force compared with the Mason-Allen configuration but was not statistically different from the luggage-tag configuration. Although not significant, the mattress configuration trended toward higher load-to-failure force compared with the luggage-tag. Clinical Relevance: The horizontal mattress stitch may be the biomechanically superior configuration in plantar plate repairs.